The Impact of Fiqih Ibadah Materials on Amaliyah of Vocational High School Students - Eka Satriani; Ahmad Putra (Journal of Islamic Education Students, 2021)
This study aims to determine the impact of fiqh ibadah (worship fiqh) material on the amaliyah (worship practice) of the 287 XII grade students at SMKN 1 Kinali, during the Covid 19 pandemic, because globally a third of the earth is experiencing the disaster. This research was conducted using a qualitative method with a case study design. All data were taken using in-depth interviews to fifteen informants who were selected using the purposive sampling technique. The researcher also took data through documentation and observation. All data were then analyzed by thematic and document analysis. Overall the results show that there are five kinds of mahdhah and ghairu mahdhah worship carried out by SMK students as routine activities such as praying, fasting, giving alms, caring for fellow humans, and improving religious understanding.Â Â